Geotechnical and Mechanical Characterization of Lateritic Soil Improved with Crushed Granite - Marie Thérèse Marame Mbengue; Abdou Lawane Gana; Adamah Messan; Anne Pantet (Salehan Institute of Higher Education, 2022)
Since many years, road infrastructures in West Africa are most often subject to premature degradations despite the large number of studies. This problem is often due to the poor control of the behaviour of materials used for the pavement, but also to the scarcity of good quality materials. Nowadays, with economic development, there is a necessity for road infrastructures of good quality. In this framework, the main objective was to study the vertical geotechnical variability of the gravelly lateritic soil from the Saaba site in Burkina Faso and to improve their performances by adding crushed granite. The results show that the physical properties of the soils are almost identical depending on the depth. However, a small difference in the mechanical properties was observed. Due to their poor characteristics, these materials cannot be used for the sub-base layer according to the pavement design guide for tropical countries, CEBTP [1]. In order to improve their geotechnical and mechanical characteristics, crushed granite of class 0/31.5 mm was added at different percentages: 20, 25, 30, and 35%. It appears that the plasticity index, the methylene blue value, as well as the optimal water content of the material decreased. The soaked CBR recorded a maximum relative increase of 164% (from 14 to 37%) with the addition of 20 to 30% of crushed granite. With the addition of 20 to 30% of crushed granite, Young's modulus and unconfined compressive strength also showed a clear increase of 309% (from 80 to 327 MPa) and 140% (from 0.72 to 1.73 MPa). By comparing the results with the CEBTP specifications, the addition of 30% of granites at 95% compactness allows the materials to have a CBR that exceeds the value of 30% and can be used in the sub-base layer of road pavement. The addition of 30% granite allows the materials to record an unconfined compressive strength higher than 0.5-1.5 MPa, which corresponds to lateritic soil suitable for sub-base layer according to Messou [2]. After the addition of 30% granite, the materials record a Young's modulus greater than 300 MPa and can be used as a base layer. The assessment of the improvement of mechanical performance simultaneously based on the CBR, the Young's modulus, and the compressive strength showed the contradictory evolution of the results from these different parameters. A discussion was made on the relationship between these parameters. Doi: 10.28991/CEJ-2022-08-05-01 Full Text: PDF